An ice-templated assembly strategy to construct graphene oxide/boron nitride hybrid porous scaffolds in phase change materials with enhanced thermal conductivity and shape stability for light–thermal–electric energy conversion. Issue 48 (22nd November 2016) - Yang, Jie; Tang, Li-Sheng; Bao, Rui-Ying; Bai, Lu; Liu, Zheng-Ying; Yang, Wei; Xie, Bang-Hu; Yang, Ming-Bo
Abstract : Multifunctional phase change materials for light-thermal-electric energy conversion are fabricated by an ice-templated assembly strategy. Abstract : Latent heat energy storage and release media of organic phase change materials (PCMs) are promising to utilize thermal energy coming from solar radiation for effective thermal management. However, the inherently low thermal conductivity and poor photoabsorption of organic PCMs lead to slow thermal charging/discharging rates, hindering the direct thermal energy conversion and storage. Here, we demonstrate that multifunctional PCMs with high thermal conductivity, improved shape-stability and efficient light–thermal–electric energy conversion can be fabricated by introducing polyethylene glycol (PEG) into graphene oxide (GO)/boron nitride (BN) hybrid porous scaffolds (HPSs) constructed via an ice-templated assembly strategy. Owing to the self-assembly of thermally conductive fillers during ice-growth, the obtained PCMs exhibit a high thermal conductivity (as high as 1.84 W m −1 K −1 at 19.2 wt% of BN), which is much higher than that of the composites fabricated by the solution blending method. Furthermore, the obtained composite PCMs with high energy storage density and excellent thermal stability can also be utilized to realize efficient light-to-thermal and light-to-electric energy conversion and storage, providing promising application potential in advanced energy-related devices and systems for solar energy utilization and storage.